Analysis of Learning Style of Phase E students at MAN 1 Jombang - Cahyati, Ayuni Eka; Ami, Mucharommah Sartika (APPLICATION: Applied science in Learning Research, 2024)
Students' learning styles are considered very important for the learning process and results learning, besides that, teachers also have an important role in implementing the learning process to students who have adapted to their learning styles. From the research that has been done The aim was to identify and analyze the learning styles of phase E students at Madrasah Aliyah Negeri 1 Jombang. In this research This is called descriptive research. This research was carried out by interviewing teachers and then providing information questionnaire/questionnaire to students, which is the questionnaire contains several statements that have been adapted to learning style theory, namely visual, kinesthetic and auditory. In this study there were 47 students who filled out the questionnaire and The results obtained were that of the 47 students, 12 of them had different learning styles visual, 16 of them have an auditory learning style, and 16 students have a learning style kinesthetic learning, apart from that, there were also 3 students who had more than one learning style, namely visual and kinesthetic and 1 student had the visual auditory kinesthetic learning style at the same time. It can be seen that the kinesthetic learning style dominates the learning style other. Because basically, students have characteristic ways of receiving more than one piece of information, but still only one way will stand out more in each student. Based on these results, it is stated that the way of learning that each person has Students will of course be different.